Electronic Circuit Analysis and Design: MultiSIM Second Edition - Donald A. Neamen (McGraw Hill Higher Education, 2001)
File program dalam bentuk: Gambar, Video (AVI), PDF, Internet (html), dll; Isi: ACROINST, BROCURE, Documentation, Msminst (setup, system, VHDS demo, dll), Samples (ch 1-17), UNBIST (Ultiboard dll), URINST (Ultiroute dll), Videos, dll; Judul dalam kemasan.